Synthesis of thermal insulating polyurethane foams from lignin and rapeseed based polyols: a comparative study - Kurańska, M. (2018)
Nowadays, a large number of polyurethane (PU) system modifications relies on the use of different bio-polyols. In this context, two bio-based polyols, one synthesized from lignin and one from rapeseed oil were evaluated in the replacement of a petrochemical polyol at an amount of 10–30 wt.% in rigid polyurethane foam formulations (RPU). The lignin-based polyol was produced by oxypropylation from an organosolv lignin (ALCELL) and the rapeseed oil-based one prepared by a two-step method of epoxidation followed by oxirane ring opening with diethylene glycol. The replacement of the petrochemical polyol with the lignin bio-polyol increased the reactivity of the reactive mixtures, while the rapeseed oil bio-polyol gave the opposite effect. This was confirmed by the respective changes observed in the dielectric polarization of the reactive mixtures together with the maximum temperature achieved in the foam core during the foaming process. The foams modified with the tested bio-polyols had both lower apparent density (40–45 kg/m3) and closed cell content (86–89%), comparatively with a reference foam. The replacement of petrochemical polyol with the bio-polyols up to 30 wt% caused, in the modified foams, a slight decrease of the compressive strength. Moreover, the introduction of the bio-polyols into PU formulations generally did not influence the thermal conductivity coefficient that was around 23 mW/m·K for the obtained materials.